Implementing classroom action research to strengthen argumentation skills: training for chemistry educators in Mojokerto - Amiq Fikriyati; Rusmini; Muchlis; Rudiana Agustini; Utiya Azizah; Harun Nasrudin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Improving teacher competency is more effective when supported by continuous professional development. This Community Service Program continues previous activities in 2024, which focused on training chemistry teachers to develop argumentation-based questions. Although teachers can now construct such questions, challenges remain in classroom implementation, especially in applying strategies and assessing their impact on students’ argumentation skills. To address this, the program introduces Classroom Action Research (CAR) based on argumentation skills. The goal is to equip chemistry teachers with practical knowledge and skills to design and implement learning that fosters argumentation through CAR. The program includes training, group discussions, tests and questionnaires, mentoring in CAR planning, implementation practice, and reflection. Results show improved teacher understanding of argumentation structures, CAR stages, and enhanced ability to design contextual and reflective learning to develop students’ argumentation skills. This program supports the sustainable development of argumentation-based learning to improve the quality of chemistry education in line with 21st-century demands. This program demonstrates an effective model for sustaining argumentation-based learning in chemistry education.